Intermitten Fasting and Caloric Restriction in Adults: Differential Effect on Cognitive Function and Neurobiological Outcomes: A Systematic Review - Marviano, Fajri Ramadhan; Apriyelita, Annisa (Jurnal Biologi Tropis, 2026)
Intermittent fasting (IF) and caloric restriction (CR) represent dietary strategies based on energy intake limitation that have been widely investigated for their potential benefits on metabolic processes and brain performance. This systematic review aims to evaluate the relationship and effects of IF and CR on cognitive function and neurobiological outcomes related to brain inflammation in adult populations. Literature retrieval was carried out through the PubMed and ScienceDirect databases using inclusion criteria structured by the PICOS framework, resulting in 10 eligible studies. The analysis showed that several studies reported improvements in cognitive function following IF/CR interventions, which were thought to be associated with enhanced neurogenesis and reduced inflammatory markers. However, several other studies found no significant differences compared with the control groups, which may have been influenced by the relatively short duration of the interventions, limitations in cognitive assessment methods, and the relatively healthy characteristics of the study populations. Therefore, the neurobiological mechanisms underlying the effects of these dietary interventions cannot be fully explained. In summary, IF and CR show promise as nutritional interventions to promote cognitive function in adults; however, the current body of evidence is still heterogeneous, highlighting the need for future studies employing more rigorous methodologies and extended intervention durations.